Analysis of the work, health and well-being experience of immigrant personal support workers in minority language contexts in Canada: Scoping review protocol - Léonel Philibert; James Plaisimond; Judith Lapierre; Soutongnoma Safiata Kaboré; André Nguwo Osomba; Luula Mariano; Frédéric Bergeron; Gbetogo Maxime Kiki; Gisèle Mandiangu Ntanda (PLoS ONE, 2026)
Background The aging Canadian population has led to an increase in Canada’s use of home and community care services. In this context, the healthcare system relies heavily on personal support workers who work in various healthcare settings. A significant proportion of these workers are immigrants, and many live in linguistic minorities. Despite their pivotal role, the experiences and working conditions of these personal support workers are underrepresented in the scientific literature, specifically in intersectional analyses. This scoping review aims to examine the work experiences, health conditions, and well-being of immigrant personal support workers in Canada who work in a minority language setting. Eligibility criteria Studies addressing the work experiences, health conditions, and well-being of immigrant personal support workers in Canada who work in a minority language setting, and those published in English or French. There will have no restrictions on publication date. Method This review will follow the JBI recommendations for scoping reviews and incorporate the PRISMA-ScR checklist. We will develop an adapted search strategy for five relevant databases (Medline [Ovide], Web of Science, Embase, CINAHL, and Google Scholar). Two independent reviewers will select full-text articles based on pre-established inclusion criteria and extracted relevant data. The results will be presented in accordance with the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-analyses Extension for Scoping Reviews) guidelines. This scoping review contributes to expanding knowledge about the professional, health, and social realities of immigrant PSWs in Canada’s linguistic minority communities.